COVID-19 in forensic psychiatry settings: The unique vulnerability of patients in secure services. (13th April 2021) - Basrak, N.; Mulcrone, N.; Sharifuddin, S.; Ghumman, Z.; Bechan, N.; Mohamed, E.; Murray, M.; Rajendran, H.; Gunnigle, S.; Nolan, M.; Quane, T.; Terao, M.; et al.
Abstract : Introduction: Secure forensic mental health services treat patient with high rates of treatment resistant psychoses, typically schizophrenia. These groups have high rates of obesity and medical co-morbidities. Population based studies have identified high risk groups in the event of SARS-CoV-2 infection, including those with long term medical conditions. Objectives: The aim of this study was to compare the vulnerability to serious adverse outcome in the event of COVID-19 infection in a forensic psychiatric patient population. Methods: All patients of a complete National Forensic Mental Health Service (n=141) were rated for risk of adverse outcome in the event of SARS-CoV-2 infection, using two structured tools, the COVID-AGE tool and the COVID-Risk tool. Results: Eighty-two patients (58.2%) met criteria for obesity, 32 had type II diabetes and 28 were hypertensive. Mean chronological age was 45.5 years (SD 11.4, median 44.1), while mean COVID-AGE was 59.1 years (SD 19.4, median 58.0), mean difference 13.6 years (SD 15.6) paired t=10.9, df=140, p=0.000. Three patients (2.1%) were chronologically over 70 years compared to 40 (28.4%) with a COVID-AGE over 70 (X2=6.99, df=1, p=0.008, Fishers exact test p=0.027). Conclusions: These risk assessments may identify the extent of increased risk among a uniquely medically vulnerable patient group. Patients in secure forensic psychiatric services represent a high-risk group for adverse outcomes in the event of SARS-COV-2 infection. Population based cocooning and self-isolating guidance based on chronological age may not be sufficient. There is an urgent need for better physical health research and treatment in this group.